MITIGASI RISIKO BENCANA BANJIR DI DESA ANDONGSARI KECAMATAN AMBULU KABUPATEN JEMBER - Galih Wicaksono; Rendy Setiawan; Krisnamurti Krisnamurti; Anik Suwandari (Batara Wisnu : Indonesian Journal of Community Services, 2023)
This activity program is in partnership with the Andongsari Village Government, which is one of the villages supported by the University of Jember. The main problem in this village is the lack of knowledge and equipment that focuses on reducing the impact of flood risk, which means that flood events cannot be predicted accurately by the community. Based on these problems, the proposing team offered several solutions such as providing grants of equipment related to flood management, guidebooks for dealing with floods, training on early warning systems for flood disasters and efforts to introduce and preserve the environment. The method of implementing this activity is in several stages, which generally include: funding for equipment grants, training and simulation, mentoring, and activity evaluation. With the activities and equipment grants that have been carried out, the Village Government feels helped and has a better understanding of flood disaster risk mitigation, so that in the future it will be better prepared when facing floods